Active Power Loss Reduction by Particle Swarm Optimization Algorithm - Lenin, Kanagasabai (International Journal of Computer Sciences and Engineering, 2019)
This work presents Particle swarm optimization (PSO) algorithm for solving optimal reactive power problem. PSO is an optimization tool based on a population, where each member is seen as a particle, and each particle is a potential solution to the problem under analysis. Each particle in PSO has a randomized velocity associated to it, which moves through the space of the problem. However, unlike genetic algorithms, PSO does not have operators, such as crossover and mutation. PSO does not implement the survival of the fittest individuals; rather, it implements the simulation of social behaviour. Projected Particle swarm optimization (PSO) algorithm has been tested in standard IEEE 300 bus system and simulation results show the better performance of the proposed algorithm in reducing the real power loss.